The effect of mental training on muscle damage, stress, and immune response biomarkers in tennis athletes* - Hepsert, Sezgin; Sezer, Burcu Sıla; Genç, Harun; Türkmen, Mustafa; Dalkılıç, Semih; Kılıç, Yakup (BioMed Central Ltd, 2026)
Background: The aim of this study is to investigate the effects of a 6-week mental training programme administered to tennis players on creatine kinase, immunoglobulin A, alpha-amylase and aspartate aminotransferase, selected as salivary biomarkers. Methods: The study was conducted as a randomized controlled trial using a pre-test–post-test parallel-group design. A total of 20 tennis players were randomly assigned to either the experimental (n = 10) or control (n = 10) group. Whilst both groups continued their routine tennis training three days a week, the experimental group additionally underwent the mental training programme three days a week prior to their tennis training sessions. The data were analysed using a Linear Mixed-Effects Model (LMM) to examine the effects of group, time, and the group × time interaction. Post hoc pairwise comparisons were performed using Bonferroni-adjusted tests where appropriate. Results: The analysis results indicated that group × time interactions were significant for the parameters creatine kinase, immunoglobulin A, alpha-amylase and aspartate aminotransferase (p<0.05). In particular, whilst an increase in IgA levels was observed in the experimental group, CK and AST values were found to be lower or stable compared to the control group. It was also found that the stress response in sAA levels became more stable in the experimental group. Post-hoc analyses showed that there was no significant difference between the groups in the pre-test (p>0.05), but significant differences emerged in favour of the experimental group in the post-test (p<0.05). However, although the main effects of group and time on creatine kinase, alpha-amylase and aspartate aminotransferase levels were not significant, the finding that the group × time interaction was significant indicates that the effect of the intervention emerged in the patterns of change over time rather than in the absolute values. Conclusions: This suggests that the experimental group’s biomarker responses changed in a different direction and magnitude compared to the control group, and that mental training dynamically modulates physiological adaptation processes. In conclusion, it was determined that a 6-week mental training programme significantly modulated salivary biomarkers associated with muscle damage, immune response and stress response in tennis players. These findings demonstrate that mental training is an effective intervention method that supports not only psychological but also physiological and immunological adaptation in athletes. © The Author(s) 2026.
Keywords: Athletic Recovery; Immune Response; Mental Training; Stress Biomarkers